Construction of Hell as a Non-Physical Condition through Illocutionary Acts in Sartre’s No Exit - Fariz Maulana Alrizal; Almira Irwaniyanti Utami (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2026)
This study examines how the concept of hell is constructed as a non-physical condition through illocutionary acts and interpersonal conflict in Jean-Paul Sartre’s drama No Exit. While previous research on the play has predominantly focused on philosophical themes such as existential freedom and the absurdity of human life, the specific linguistic mechanisms—particularly how characters use language to exert power and induce suffering, have received less attention. Addressing this gap, this research highlights how verbal interaction functions as the primary instrument of torment. Using Searle’s (1976) classification of illocutionary acts (assertive, directive, commissive, expressive, and declarative), this study analyzes selected utterances from the three main characters: Garcin, Inéz, and Estelle. The analysis also considers the perlocutionary effects of each utterance to examine the dynamic discourse battles among the characters. The findings show that out of five illocutionary acts, four are actively utilized to construct this condition. Assertive acts establish fixed and inescapable judgments that trap the characters in a shared reality, while directive acts consistently fail, revealing that the characters cannot mentally or physically avoid one another. Furthermore, expressive acts expose involuntary emotions that cannot be concealed from the judgment of others, and commissive acts demonstrate that promises fail to guarantee connection or safety. The fifth act, declarative, is notably absent, emphasizing the characters' complete lack of authority to alter their environment. These acts demonstrate that hell in the play is not a place of physical torture, but a psychological state continuously produced through inescapable verbal interaction. This study contributes to the understanding of how pragmatic features of language, especially illocutionary acts, can construct social and psychological meaning within literary works.